Vigabatrin: Lessons Learned From the United States Experience. Issue 4 (December 2018) - Foroozan, Rod
Abstract : Abstract: Vigabatrin was introduced as an antiseizure medication in the United Kingdom in 1989 and was extensively used until 1997 when concerns arose regarding peripheral visual field loss. When the drug was approved in the United States in 2009, it carried a black box warning for the risk of permanent visual loss, and the pharmaceutical company was mandated to create a drug registry to assess for visual deficits. The vigabatrin drug registry has documented a relatively large percentage (37%) of preexisting, baseline visual deficits and a paucity (2%) of potential new visual findings. The vigabatrin vision study, a prospective, longitudinal, single-arm, open-label study, confirmed that adult patients with refractory complex partial seizures had a large number of visual deficits at baseline. An unexpected finding during the first year of therapy with vigabatrin was an increase in retinal thickness on optical coherence tomography. The experience from vigabatrin in the United States emphasizes the importance of baseline eye findings when considering the potential of drug toxicity involving the visual pathways. Abstract : Supplemental Digital Content is Available in the Text.